A Program of Exposure and Training for Seminary Students in an Institution for the Mentally Retarded, Kansas Neurological Institute, November, 1966 - Perske, Robert (Journal of religion, disability & health, 2003)
While they have often been accused of being detached from the rest of the world, seminaries have a unique opportunity to introduce future pastors to persons with mental retardation, which are an important community which has often been ignored by churches. This could occur through intentional friendships, developed under careful supervision, between the seminary student and a few people with mental retardation. Additionally, the seminarian could learn about the issues pertinent to people with mental retardation through a week long seminar and continual reflection, as well as a period in which the seminary student lives on the ward with his or her friends. This in-depth exposure to the lives of those with mental retardation could expand the ability of the seminary student to engage important issues, and further connect the church to the issues confronting persons with mental retardation.